La orientación en Educación Secundaria - Lucio-Villegas de la Cuadra, Mercedes (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 1999)
This article gives an overall description of the system of orientation which makes it possible to discern the principles, objectives, structure, organization and functions in the different stages that principles, objectives, structure, organization and functions in the different stages that go to make up Secondary Education in Spain. And specifically in the area of the Ministry of Education and Culture and in the actual situation existing in Secondary Education.